Establishment of ultrasound-guided stellate ganglion block in rats - Lin, Shi-zhu; Chen, Lu; Tang, Yi-jie; Zheng, Cheng-jie; Ke, Peng; Chen, Meng-nan; Wu, Hai-xing; Chen, Yu; Qiu, Liang-cheng; Wu, Xiao-dan; Zeng, Kai (Frontiers in Neuroscience, 2023)
Background A novel protocol for accurate stellate ganglion block under ultrasound guidance was designed in rats. This technique raises the success rate of stellate ganglion block and reduces the incidence of brachial plexus and vagus nerve block. Methods Fifty-six Sprague-Dawley were randomly divided into an ultrasound-guided group (n = 28) and a blind technique group (n = 28). The rats in the blind technique group were injected with 1.5% lidocaine mixed with methylene blue after signs of brachial plexus stimulation were elicited. The lateral side of the cephalic brachial vein was located under the first rib, where lidocaine was injected into the rats in the ultrasound-guided group. The up-and-down sequential method of Dixon was used to determine the minimum effective volume for stellate ganglion block in rats. Furthermore, we calculated the required operative duration of the two methods and observed the difference in the lidocaine diffusion range between the two groups. Results The minimum effective volume for stellate ganglion block in the ultrasound-guided group was 0.040 ml, and the 95% CI was 0.026–0.052 ml. In the blind technique group, the minimum effective volume was 0.639 ml, and the 95% CI was 0.490–0.733 ml. Within the 95% CI of the lowest effective volume, the incidence of brachial plexus block as a complication of stellate ganglion block under ultrasound guidance was 10.00%. Conclusion Stellate ganglion block under ultrasound guidance is more accurate than blind detection, which the incidence of complications of stellate ganglion block under ultrasound guidance was significantly lower than under blind detection; the rate of methylene blue staining in the vagus nerve was significantly lower under ultrasound guidance.